Critical Success Factors for Data Governance: A Theory Building Approach. Issue 2 (3rd April 2019) - Alhassan, Ibrahim; Sammon, David; Daly, Mary
ABSTRACT: The objective of this research study is to present the critical success factors (CSFs) for data governance (DG). This paper reports on a single case study where data are gathered through semi-structured interviews following the CSF approach and analyzed by applying open, axial, and selective coding techniques. The findings are presented as seven CSFs, which are ranked in order of importance. Furthermore, we highlight the need to better understand the relationships (interconnectedness) between the CSFs.